Magnetic Resonance Imaging of Seminal Vesicle Cyst Associated with Ipsilateral Urinary Anomalies - Huan-Wu Chen (Journal of the Formosan Medical Association, 2006)
Seminal vesicle cysts rarely cause symptoms. Data on long-term follow-up from childhood to adulthood are lacking. The study analyzed the magnetic resonance imaging (MRI) and follow-up results of this condition. Methods: From 1991 to 1996, seminal vesicle cyst was diagnosed in 13 boys (mean age, 12 years; range, 7-15 years), six of whom had long-term follow-up data. The clinical symptoms and MRI findings at diagnosis and at follow-up were analyzed. Results: The seminal vesicle cyst was on the right side in six patients and on the left in seven. The size varied, ranging from 1.0 × 1.3 × 1.4 to 4.4 × 3.1 × 3.6 cm. All showed high signal intensity on T2-weighted images but variable signal intensity on T1-weighted images. Associated urinary tract anomalies included renal anomalies (dysplasia in 2 patients, agenesis in 11), ectopic ureteral orifice (11), hydroureter (6), and vertebral anomalies (2). One of the six patients with follow-up had repeated urinary tract infection and underwent surgical resection of the cyst 8 years after the diagnosis. The other five had no symptoms during the follow-up period. Three of the six patients had repeat MRI after a median of 11 years, which showed slight cyst enlargement and increased T1-weighted signal intensity. Conclusion: Most seminal vesicle cysts were asymptomatic and did not change during long-term follow-up. MRI is a powerful tool for detecting seminal vesicle cysts and in delineating associated congenital anomalies of the urogenital tract.